2004
DOI: 10.1086/382959
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus (HCV) Diversity in HIV‐HCV–Coinfected Subjects Initiating Highly Active Antiretroviral Therapy

Abstract: Because of increased mortality and reduced treatment response rates in subjects coinfected with human immunodeficiency virus (HIV) and hepatitis C virus (HCV), understanding the selection pressures underlying the evolution of HCV is important for the development of strategies to control both viruses. We therefore investigated diversity of HCV in 11 HIV-HCV-coinfected subjects initiating highly active antiretroviral therapy (HAART). Distinct categories of HCV virologic response to suppression of HIV were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 51 publications
(50 reference statements)
5
42
1
Order By: Relevance
“…HIV-HCV coinfection was associated with reduced HVR1 diversity compared to monoinfection, and our data help us to understand why this point has been controversial in previous literature (4,27,31,34,36,39,43). There was considerable variation in HCV diversity among subjects within each group, which is particularly evident thanks to the depth of the pyrosequencing data, suggesting that factors in addition to HIV coinfection also affect diversity.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…HIV-HCV coinfection was associated with reduced HVR1 diversity compared to monoinfection, and our data help us to understand why this point has been controversial in previous literature (4,27,31,34,36,39,43). There was considerable variation in HCV diversity among subjects within each group, which is particularly evident thanks to the depth of the pyrosequencing data, suggesting that factors in addition to HIV coinfection also affect diversity.…”
Section: Discussionsupporting
confidence: 51%
“…Approximately one-third of HIV-infected patients are coinfected with HCV (35), and HIV coinfection increases HCV-related liver diseases (10), raising the question of how HIV coinfection affects the structure and evolution of HCV populations. One possibility is that immune impairment due to advanced HIV infection results in reduced immune pressure on HCV populations (4,18) and thus in diminished HCV diversity. To investigate this issue, we compared HCV sequence diversities in HIV-HCV-coinfected and HCV-monoinfected patients.…”
Section: Hcv Samples Studiedmentioning
confidence: 99%
“…They found increased viral diversity and complexity in patients on long-term HAART but no changes were evident among patients treated short-term. Similarly, Blackard et al 55 observed increase in HVR1 diversity in 11 patients treated for 48 weeks. However, no adjustments for covariates were made in either of these 2 studies.…”
Section: Discussionmentioning
confidence: 78%
“…Gel-purified PCR products were ligated into the pGEM-T Easy vector, and a median of 10 plasmids per sample was sequenced. We and others have shown that analysis of ϳ10 sequences accurately and reproducibly represents intrapatient quasispecies diversity (1,20). All alignments were performed using Clustal X and compared to database references to determine the HCV genotype.…”
mentioning
confidence: 99%
“…All alignments were performed using Clustal X and compared to database references to determine the HCV genotype. Intrapatient genetic distances, Shannon entropy, and differences between nonsynonymous (dN) and synonymous (dS) rates (dN Ϫ dS) were calculated as described elsewhere (1). Codons under positive or negative selection were detected via the fixed effects likelihood (FEL) and random effects likelihood (REL) methods as implemented in the Datamonkey program (12).…”
mentioning
confidence: 99%